Problematika Pendidikan Keluarga Dalam Menanggulangi Kenakalan Remaja Di Desa Yungyang Kecamatan Modo Kabupaten Lamongan - Handayani, Risa Dwi; Junaidi, Mahbub (Jurnal Murid, 2025)
Juvenile delinquency is an act that violates norms, rules or laws in society that is committed during adolescence or the transition between childhood and adulthood. This research aims to determine the forms of juvenile delinquency, the factors that cause juvenile delinquency and how big the role of family education is. on juvenile delinquency in Yungyang Village, Modo District, Lamongan Regency. The research method used is a qualitative approach with descriptive research type. The data collection techniques used were observation, interviews and documentation. The data analysis used is data condensation, data presentation, and drawing conclusions. The results of the research show that: 1) forms of juvenile delinquency include smoking, coming home late at night, speeding on the street, fighting with peers, drinking alcohol 2) the causes of juvenile delinquency can vary, including family environmental factors, peer factors, or even internal factors. Adolescents who experience emotional or less stable families also tend to be more susceptible to committing juvenile delinquency. 3) The role of family education in overcoming juvenile delinquency is very important in preventing and overcoming juvenile delinquency because parents are responsible for supervising children's activities.